Past, present and future—sample environments for materials research studies in scattering and spectroscopy; a UK perspective. (22nd September 2021) - Terrill, Nicholas J; Dent, Andrew J; Dobson, Barry; Beale, Andrew M; Allen, Lisa; Bras, Wim
Abstract: Small angle x-ray scattering and x-ray absorption fine structure are two techniques that have been employed at synchrotron sources ever since their inception. Over the course of the development of the techniques, the introduction of sample environments for added value experiments has grown dramatically. This article reviews past successes, current developments and an exploration of future possibilities for these two x-ray techniques with an emphasis on the developments in the United Kingdom between 1980–2020.